The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s0021859613000415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-linear models to describe the lactation curves of milk yield and composition in Iranian Holsteins

Abstract: In order to describe the lactation curves of milk yield (MY) and composition, six non-linear mathematical equations (Wood, Dhanoa, Sikka, Nelder, Hayashi and Dijkstra) were used. Data were 5 535 995 test-day records for MY, fat (FC) and protein (PC) contents and somatic cell score (SCS) from the first three lactations of Iranian Holstein cows that were collected on 2547 dairy herds in the period from 2000 to 2011 by the Animal Breeding Center of Iran. Each model was fitted to monthly production records of dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Variations between the lactation curve characteristics of primiparous and multiparous buffaloes are likely to be responsible for the significant difference between goodness of fit of the models for the different lactations. In addition, the difference between fit of models may have arisen from the variations in mathematical functions of the models (Ghavi Hossein-Zadeh, 2014a). Consistent with the current study, Dimauro et al (2005) showed that the models commonly used to fit the lactation curve in dairy cattle are able to describe with a high degree of accuracy average curves of water buffaloes.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Variations between the lactation curve characteristics of primiparous and multiparous buffaloes are likely to be responsible for the significant difference between goodness of fit of the models for the different lactations. In addition, the difference between fit of models may have arisen from the variations in mathematical functions of the models (Ghavi Hossein-Zadeh, 2014a). Consistent with the current study, Dimauro et al (2005) showed that the models commonly used to fit the lactation curve in dairy cattle are able to describe with a high degree of accuracy average curves of water buffaloes.…”
Section: Resultssupporting
confidence: 83%
“…The state of pregnancy results in a markedly reduced MY for lactating buffalo cows, as happened in dairy cattle before the development of selection programs for the improvement of MY (Coulon et al, 1995). Latest peak production observed in first lactation for most models in the current study, while third lactation buffaloes generally had the earliest day of peak production and this might be explained by the milk secretary tissue in primiparous buffaloes taking longer to reach its peak activity than in multiparous buffaloes (Ghavi Hossein-Zadeh, 2014a). Different persistency measures and 305-day MY for average standard lactations of buffaloes according to parity class, predicted by different equations are presented in Table 9.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Several authors have shown variations in the general shape of the lactation curve (e.g. Landete-Castillejos & Gallego 2000;Fathi Nasri et al 2008;Ghavi Hossein-Zadeh 2014), the most common shape being a rapid increase after parturition to a peak a few weeks later, followed by a slow decrease until the cow is dried off. The other shape is a gradual decline from calving.…”
Section: Resultsmentioning
confidence: 99%